The impact of free farmland transfer on the adoption of conservation tillage technology -- empirical evidence from rural China - Jingwen Xu; Jia Chen; Shuang Zhao (Heliyon, 2022)
At present, there are a large number of free farmland transfer without monetary or physical rents in rural China. It is relatively worthwhile to verify whether the transferees who transfer in farmland for free, the actual operators of farmland, would adopt the conservation tillage technology (CTT), which is crucial in protecting farmland quality and improving agricultural production efficiency. Based on the data of 527 plots surveyed by China Land Economic Survey (CLES) in Jiangsu Province in 2020, this paper employs Negative Binomial Regression (NBR), Poisson Regression with Endogenous Treatment Effects (ETPR) and Endogenous Switching Regression (ESR). Results show that: (1) Compared with the transferees who transfer into farmland with compensation, the free transfer is not conducive to the transferees' adoption of CTTs such as straw mechanical returning, soil testing and formulated fertilization. Specifically, the total number of technology adoptions by transferees who transfer in farmland without compensation is decreased by 39.54%. The result is still robust after replacing the dependent variable. (2) Further heterogeneity analysis results of different types of technologies show that the number of labor-saving CTTs such as straw mechanical returning adopted by the transferees of free transfer decreases by 11.55%, and the number of labor-intensive tillage technologies such as soil testing and formulated fertilization decreases by 83.20%. Thus, free transfer has a stronger inhibitory effect on the transferees’ adoption of labor-intensive CTTs. Therefore, for the most developing countries including China, the governments should continue to improve the farmland factor market oriented by price mechanism and implement targeted conservation tillage technology according to the different degree of transfer marketization in different places.